The Role of School Principal Leadership in Improving Teamwork and Teacher Performance Motivation at SMK N 5 Merangin - Suryarti, Epi; Muazza, Muazza; Masbirototni, Masbirototni (Mudir : Jurnal Manajemen Pendidikan, 2024)
Abstract: This qualitative research aims to describe the role of the principal in improving teamwork and teacher performance motivation at SMK Negeri 5 Merangin. The research method is a field study, based on observation and in-depth interviews with key informants. The results of this study state that the role of the principal motivates teacher performance by doing things such as giving awards and recognition of the results of the teacher's work providing space to innovate to the teachers, providing direction and coaching, providing authority, giving attention, giving picnics and incentives for teachers who excel. The principal's leadership style that applies to subordinates is a consultative, participatory, and educative leadership style. It can be concluded that principals can increase teacher performance motivation.  Improving the quality of education affects many factors, one of which is the ability of teachers which is very important. For this reason, the role of the Principal of SMKN 5 Merangin in improving teamwork is running smoothly, namely acting as a problem solver, through coordination meetings every two weeks to monitor the performance of teachers or program implementers and find out the obstacles faced, even personally with teachers or even parents of students through chat applications.  In the role of increasing teacher performance motivation, namely giving rewards or gifts to subordinates aims to motivate individuals for satisfactory performance, given on the basis of sacrifices of time, energy and thought. The leadership model uses a transactional leadership model, and also applies a participatory leadership model.